LAS AGENCIAS DE VIAJE: DE LAS COMISIONES POR VENTA DE PASAJES A LOS COBROS POR SERVICIOS “FEES” - Domingo Begazo, José (2007)
The globalizaton, as a dynamic element of the global economy , has generated in the world business a new dyamic and highly competitive managerial instrument. This is applied to the management of the airlines that have readjusted the commissions of the Travel Agencies from 20% to 1%. So, in order to survive, travel agencies have to create a new charge for his customer servces denominated: FEES.